Tourism branding : communities in action / Liping A Cai, William C Gartner, Ana María Munar - Cai, Liping A
Academic studies have predominantly treated destination branding as a marketing phenomenon that happens to involve tourists as customers in a marketplace. Tourism Branding: Communities in Action, the first volume in a new and exciting book series, considers a traditional marketing subject from multidisciplinary perspectives.